2016
DOI: 10.1021/jacs.6b05723
|View full text |Cite
|
Sign up to set email alerts
|

High and Reversible Ammonia Uptake in Mesoporous Azolate Metal–Organic Frameworks with Open Mn, Co, and Ni Sites

Abstract: A series of new mesoporous metal-organic frameworks (MOFs) made from extended bisbenzenetriazolate linkers exhibit coordinatively unsaturated metal sites that are responsible for high and reversible uptake of ammonia. Isostructural Mn, Co, and Ni materials adsorb 15.47, 12.00, and 12.02 mmol of NH3/g, respectively, at STP. Importantly, these near-record capacities are reversible for at least three cycles. These results demonstrate that azolate MOFs are sufficiently thermally and chemically stable to find uses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
249
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 263 publications
(257 citation statements)
references
References 28 publications
6
249
1
1
Order By: Relevance
“…This result is indicative of a selective and strong interaction of NH3 molecules with SION-10′ due to chemisorption (presence of active Cu(II) centers) and physisorption (narrow pores of SION-10′), and places SION-10′ among materials with the highest NH3 capacity reported up to date. [9,11] Interestingly, the color change experienced by the NH3 loaded SION-10′ was also observed when the as-made SION-10 was exposed to NH3 vapors. The immersion of the blue SION-10⊃NH3 in liquid water resulted in the isolation of a green material suggesting that SION-10 could potentially be recovered.…”
Section: Sion-10′mentioning
confidence: 87%
See 2 more Smart Citations
“…This result is indicative of a selective and strong interaction of NH3 molecules with SION-10′ due to chemisorption (presence of active Cu(II) centers) and physisorption (narrow pores of SION-10′), and places SION-10′ among materials with the highest NH3 capacity reported up to date. [9,11] Interestingly, the color change experienced by the NH3 loaded SION-10′ was also observed when the as-made SION-10 was exposed to NH3 vapors. The immersion of the blue SION-10⊃NH3 in liquid water resulted in the isolation of a green material suggesting that SION-10 could potentially be recovered.…”
Section: Sion-10′mentioning
confidence: 87%
“…[3] NH3 is an important raw material for the manufacturing of large numbers of chemicals including fertilizers, dyes, plastics, and pharmaceuticals, [4] and is considered as a potential carbon-free green fuel due to its high energy density and its lower cost of production, storage, and delivery compared to hydrogen. [5] Both the danger and usefulness of NH3 have motivated researchers to develop economical and responsive materials that can selectively detect and capture NH3; for example, NH3 sensors based on catalytic metals [6] and conducting polymers [7] have been reported, whilst porous materials such as activated carbons, [8] organic polymers, [9] covalent organic frameworks, [10] and MOFs [11] are known as efficient NH3 sorbents. MOFs are crystalline materials prepared by the selfassembly of metal ions or clusters with organic ligands to form porous extended structures.…”
Section: Adsorbent For Ammoniamentioning
confidence: 99%
See 1 more Smart Citation
“…Four families of materials that provide this breadth are M 2 (DOBDC)(DMF) 2 (M = Mg 2+ , Mn 2+ , Fe 2+ , Co 2+ , Ni 2+ , Cu 2+ , Zn 2+ ), 17–24 M 2 (DSBDC)(DMF) 2 (M = Mn 2+ , Fe 2+ ), 4,5 M 2 Cl 2 (BTDD)(DMF) 2 (M = Mn 2+ , Fe 2+ , Co 2+ , Ni 2+ ), 25 and M(1,2,3-triazolate) 2 (M = Mg 2+ , Mn 2+ , Fe 2+ , Co 2+ , Cu 2+ , Zn 2+ , Cd 2+ ). 14,15 The first three families of MOFs display honeycomb structures with 1D tubular pores, whereas the M(1,2,3-triazolate) 2 materials exhibit cubic structures with three-dimensional pore networks ‡…”
Section: Introductionmentioning
confidence: 99%
“…Key framework features which improve adsorption properties need to be identified and optimised for the development of better future materials. For example, many studies have shown that the presence of coordinative-unsaturated metal centres tends to enhance total uptake of gases such as hydrogen [1][2][3], methane [4] and ammonia [5], among others, and can also contribute to guest selectivity in the presence of gas mixtures [6]. These "bare" metal sites interact strongly with many guest molecules, yielding higher binding energies and often resulting in denser arrangements of guests in the pores of the sorbent material.…”
Section: Introductionmentioning
confidence: 99%